Observations and a model for the infrared continuum of Centaurus A - Alexander, D; Efstathiou, A; Hough, J; Aitken, D; Lutz, D; Roche, P; Sturm, E (1999)
We present ISOSWS, ISOPHOT_S and 8-13 μm observations of Centaurus A which show prominent PAH and silicate features. These and other data are used to construct a model for the infrared continuum. We find that, in a small nuclear aperture (∼4 arcsec, ∼60 pc), the spectral energy distribution is characteristic of emission from a starburst and dusty AGN torus; in larger apertures, additional components of cirrus and starburst emission are required. The model components are based on the radiative transfer models of Efstathiou et al. which include multiple scattering and the radiative effects of a dust-embedded source with a distribution of grain species and sizes. The torus component is modelled in terms of a tapered dusty disc centrally illuminated by a quasar-like source. The cirrus and starburst components are, respectively, modelled in terms of diffuse dust illuminated by the interstellar medium and an ensemble of optically thick molecular clouds centrally illuminated by hot stars. These latter components additionally include emission from small graphite particles and PAHs. Based on our overall model, the torus diameter is estimated to be 3.6pc and the best inclination angle of the torus is 45°. We present independent observational evidence for this structure. This result has implications for the detectability of tori in low-power AGN and for the use of the IRAS 60/25-μm flux ratio as an indicator of the torus inclination.